Protective association of HLA‐DRB1*04 subtypes in neurodegenerative diseases implicates acetylated tau PHF6 sequences. (20th December 2022) - Guen, Yann Le; Luo, Guo; Ambati, Aditya; Damotte, Vincent; Jansen, Iris E; Yu, Eric; Nicolas, Aude; de Rojas, Itziar; Leal, Thiago Peixoto; Miyashita, Akinori; Bellenguez, Céline; Lian, Michelle Mulan; et al.
Abstract: Background: Alzheimer's disease (AD), Parkinson's disease (PD), Amyotrophic Lateral Sclerosis (ALS) and other neurodegenerative diseases are responsible for considerable morbidity and mortality. With incidence rising with aging, these also represent a growing societal challenge. Pathophysiology involves accumulation of tau (neurofibrillary tangles) and Amyloid‐β‐rich (amyloid plaques) aggregates in AD, α‐synuclein‐rich aggregates (Lewy bodies) in PD and TDP‐43 aggregates in ALS, although co‐presence of these aggregates may occur. Consensus is also growing that tau may also play a key role in PD and ALS. Method: Using genome‐wide association data, we analyzed Human Leukocyte Antigen (HLA) associations in over 176, 000 individuals with PD or Alzheimer's AD disease versus controls across ancestry groups. Result: A shared genetic association was observed across diseases at rs601945 (PD: odds ratio (OR)=0.84; 95% confidence interval, [0.80; 0.88]; p=2.2x10 ‐13 ; AD: OR=0.91[0.89; 0.93]; p=1.8x10 ‐22 ), and with a protective HLA association recently reported in ALS. Hierarchical protective effects of HLA‐DRB1 *04 subtypes best accounted for the association, strongest with HLA‐DRB1 *04:04 and HLA‐DRB1 *04:07, intermediary with HLA‐DRB1 *04:01 and HLA‐DRB1 *04:03, and absent for HLA‐DRB1 *04:05. The same signal was associated with decreased neurofibrillary tangles (but not neuritic plaque density) in postmortem brains and was more strongly associated with tau levels than Aβ42 levels in the cerebrospinal fluid. Finally, protective HLA‐DRB1 *04 subtypes strongly bound the aggregation‐prone tau PHF6 sequence, but only when acetylated at K311, a modification central to aggregation. Conclusion: An HLA‐DRB1 *04‐mediated adaptive immune response, potentially against tau, decreases PD, AD and ALS risk, offering the possibility of new therapeutic avenues.